Perlindungan Hukum terhadap Usaha Mikro, Kecil dan Menengah dalam Perspektif Keadilan Ekonomi - Yusri Yusri (Universitas Syiah Kuala, 2014)
This research aims to explore the concept of protection on micro, small and medium based on economic justice approach of John Rawls and constitutional protection of such enterprises. It is explored through John Rawls justice and the wealth management. This is descriptive qualitative research. The research applies juridical normative. The data are then analysed through qualitatively. The protection on the businesses is not implemented well. The Act on the Small and Medium Enterprise and the Qanun No. 10, 2004 is not effective in its efforts to realize the opportunity of the enterprises. Affirmative actions based on the distributive justice of John Rowls have not been implemented well by the government either in legal products or protection operational policies and the empowerment of the enterprises. Legal Protection on Micro, Small and Medium in The Perspective of Economic Justice